Renal injury, nephrolithiasis and Nigella sativa: A mini review - Parichehr Hayatdavoudi; Abolfazl Khajavi Rad; Ziba Rajaei; Mousa AL-Reza Hadjzadeh (Mashhad University of Medical Sciences, 2016)
Objective: The incidence and prevalence of kidney stone is increasing worldwide. After the first recurrence the risk of subsequent relapses is higher and the time period between relapses is shortened. Urinary stones can be severely painful and make a huge economic burden. The stone disease may increase the vulnerability of patients to other diseases such as renal failure. Medicinal herbs are rich sources of antioxidants which are increasingly consumed globally for their safety, efficacy and low price. Nigella sativa is a spice plant that is widely used for prevention and treatment of many ailments in Muslim countries and worldwide. This review aims at investigation of the effects of Nigella sativa on renal injury and stone formation. Materials and Method: The scientific resources including PubMed, Scopus, and Google scholar were searched using key words such as: nephrolithiasis, urolithiasis, kidney/renal stone, renal injury, renal failure, urinary retention and black seed, black cumin, Nigella sativa and thymoquinone.    Results: N. sativa and its main component, thymoquinone showed positive effects in prevention or curing kidney stones and renal failure through various mechanism such as antioxidative, anti-inflammatory, anti-eicosanoid and immunomodulatory effects. The putative candidate in many cases has been claimed to be thymoquinone but it seems that at least in part, particularly in kidney stones, the herbal melanin plays a role which requires further investigation to prove. Conclusion: N. sativa and its components are beneficial in prevention and curing of renal diseases including nephrolithiasis and renal damages.